A Simple Instrumentation System for Large Structure Vibration Monitoring - Didik R. Santoso (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2010)
A conventional instrumentation systems in monitoring vibration of large-scale infrastructure building such as bridges, railway, and others structural building, generally has a complex design. Makes it simple would be very useful both in terms of low-cost and easy maintenance. To make system become simple, low cost, and easy in maintenance, this paper proposes a distributed network for implementation system. The system consists of field bus topology, using single-master multi-slave architecture. Master is a control unit, built based on a PC equipped with RS-485 interface. Slave is a sensing unit; each slave is built by integrating a 3-axis vibration sensor within a microcontroller based data acquisition system. Vibration sensor is designed using the main components of a MEMS accelerometer. The software is developed for two functions; a control system hardware and a data processing. To verify performance of the developed instrumentation system, several laboratory tests have been performed. The result shows that the system has good performance.